Professional identity - Maya Maya, María Cecilia (Investigación y Educación en Enfermería, 2013)
Man has a capacity, as none other living being has, to make conscience of self and his surrounding world this conscience is the base for his nationality, cretivity and humanity. The transitions occur in virtue of successive experiences between the individual and his environment, leading to the development of personal ego, which in turn influences the evolution of the professional ego. The article introduces the reader to a subject of interest for all independent professionals, whatever their discipline, and conduces to personal reflexive ness an personal growth and the consequences for the development of the professional ego. It inveites to broaden knowledge and techniques on the subject, especially persons who have roles as counserlors and educators, and those who directly or indirectly participate in the development of human beings. Key words: Identity - nursing, Professional formation.